Difference of Frap Levels Between Preeclamptic and Normotensive Women: A Cross-Sectional Analysis from a Tertiary Care Hospital, Pakistan - Shagufta Jabbar, Sadaf Kashif, Rafia Ali, Saima Siddiq Choudhry, Mubashira Nasir Qureshi, Marya Saadullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association between FRAP levels and preeclampsia Methodology: A case control study was conducted at Social Security Teaching Hospital Multan Road, Lahore between September 2019 March 2020. A total of 309 women were enrolled in the study using the non-probability convenience sampling technique. Women at 28 weeks or higher gestation, equal to or older than 18 years of age were included in the study. Those with a history of hypertensive issues before 20 weeks of gestation or other comorbidities were excluded from the study. For antioxidative analysis, the serum FRAP was measured using colorimetric assay. Patients sociodemographic, clinical, and reproductive history were recorded. For data analysis, SPSS version 24 was used and a p-value of 0.05 or less was considered as statistically significant. Results: Preeclampsia was found in 40 (13%) pregnant women in our study. The mean age + SD for the group with pre-eclampsia was 21.56 + 4.2 years while the mean age + SD for the normotensive group was 22.12 +5.6 years. The mean + SD FRAP levels were significantly higher in women with preeclampsia than the normotensive control group (p=0.01); 684.2 + 21.2 μmole/L in the preeclampsia group and 603.1 + 15.6 μmole/L in the control group. Conclusion: The FRAP levels were significantly higher in women with preeclampsia than the normotensive women indicating a correlation between high oxidative stress and risk of developing threatening pregnancy related issues. Keywords: antioxidant, FRAP, gestational, oxidative stress, preeclampsia